The peridynamic equation and its spatial discretisation - Emmrich, Etienne; Weckner, Olaf (Mathematical Modelling and Analysis, 2007)
Different spatial discretisation methods for solving the peridynamic equation of motion are suggested. The methods proposed are tested for a linear microelastic material of infinite length in one spatial dimension. Moreover, the conservation of energy is studied for the continuous as well as discretised problem. First Published Online: 14 Oct 2010